State-corporate crime and the commodification of victimhood: the toxic legacy of Trafigura's ship of death - MacManus, Thomas (Crimes of the powerful, 2018)
Introduction: applying a criminological framework -- State-corporate crime: origins of the "ship of death" -- The Probo Koala arrives at Abidjan -- The development of the state of Ivory Coast -- Explanations for impunity -- Civil society's role -- Researching civil society in Ivory Coast -- Organisational crime and the "commodification of victimhood" -- Cover-up and denial : the battle in Britain -- Conclusion